An illustrated key to the praying mantids (Insecta: Mantodea) of India up to generic level - Kamila, A. P.; Sureshan, P. M. (Zootaxa, 2025)
A dichotomous key up to generic level is provided for the identification of Indian praying mantids (Insecta: Mantodea) with pictorial representations of 70 genera distributed over 13 families and 25 subfamilies.